Application of pomegranate (Punica granatum Linn.) fruit extract for accelerating post-tooth extraction wound healing - Intan Nirwana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Trauma occurring during tooth extraction can cause complications such as bleeding, infection, fracture and dry socket and constitutes an inflammatory response trigger. Pomegranate (Punica granatum Linn.) extract, which contains large amounts of punicallagin and ellagic acid, possesses various qualities, including; anti-inflammatory, anti-bacterial and anti-oxidant. Pomegranate extract can inhibit proinflammatory cytokine production, while also suppressing inflammation response thereby accelerating wound healing. Purpose: This study aimed to analyze the effect of pomegranate extract application to the tooth extraction wounds of Cavia cobaya (C. cobaya) on the expression of fibroblast growth factor-2 (FGF-2) and transforming growth factor β (TGF-β) on the fourth day of the wound-healing process. Methods: This study used 12 C. cobaya, divided into two groups, namely; control and treatment. The subjects were anesthetized, before their lower left central incisor was extracted and the entire socket filled with CMC-Na 3% in members of the control group and pomegranate extract in those of the treatment group. The twelve C. cobaya were sacrificed on day 4, their lower jaw subsequently being removed and decalcified for approximately 30 days. The mandibula tissue was stained using a immunohistochemical technique. FGF-2 and TGF-β were used to evaluate the healing process in the extracted tooth socket. Differences in the expression of FGF-2 and TGF-β were evaluated statistically by means of a t-test. Results: This study indicated a significant difference between the control and the treatment groups (p<0.05). The treatment group members whose sockets were filled with pomegranate extract showed high FGF-2 and TGF-β expression. Conclusion: This study confirmed that the administration of pomegranate extract to post-extraction tooth wounds of C. cobaya increases the expression of FGF-2 and TGF-β on day 4, thereby accelerating the wound healing process.